Pemaduan Teori Rasional, Empiris dan Intuisi Perspektif Muhammad Iqbal - Muhiddin Bakry (Farabi, 2015)
The forms of Islamic thought can be divided into three parts: traditional, modern, and contemporary. In general, Islamic thought patterned are dialectic (jadali), demonstrative (Burhani), intuitive (Irfani), and theosophy (wisdom, also called hikmah muta'aliyah). This paper will examine the figure of Muhammad Iqbal, one of the phenomenal modern Muslim thinkers. He has reconstructed a building of Islamic philosophy which can be equipped to individual Muslims in anticipation of Western civilization materialistic or fatalistic Eastern tradition. Philosophy of Khudi and devinity metaphysics of Iqbal able to combine rationalism, empiricism and intuitive that had been considered separate and contradictory.